Hepatoprotective activity of Dicranopteris linearis (Burm. f.) Underw. leaf methanol extract and its ethyl acetate fraction - Kamisan, Farah Hidayah (2017)
Liver disease is a major global concern with extremely poor prognosis and high mortality rate due to the lack of effective preventive or treatment options. Besides,a reliable liver protective drug with fewer side effects is still lacking in modern medicines. Therefore, attempts are perpetually being made to investigate several alternative therapies that use natural plants. In the first part of the in vivostudy, methanol extract (MEDL) of Dicranopteris linearisleaves was investigated for hepatoprotective activity against carbon tetrachloride (CCl4)-induced and paracetamol (PCM)-induced liver damage. Rats (n=6) used in the study were divided into several groups and given a daily administration of 10% dimethyl sulfoxide (negative control group), 200 mg/kg Silymarin (positive control group) or MEDL (50, 250 or 500 mg/kg) for 7 days, followed by the induction of hepatotoxicity either CCl4or PCM. Crude methanolic extracts also were further partitioned using solvents of increasing polarity: petroleum ether <ethyl acetate <water. Semi-purified partitions were called petroleum ether (PEDL), ethyl acetate (EADL) and aqueous (AQDL) extracts. In the second part of in vivo study, these partitions were assayed on PCM-induced hepatotoxicity study. All the semi-purified partitions with intermediate doses (250 mg/kg) were tested on the PCM-induced hepatotoxicity model. The best partition proceeded with another two doses of 50 mg/kg and 500 mg/kg. Blood samples and livers were collected and subjected to biochemical and microscopic analyses. The crude and all the semi-purified partitions were also subjected to antioxidant assays, 2, 2-diphenyl-1-picrylhydrazyl radical scavenging assay (DPPH), superoxide dismutase scavenging activity assay (SOD), and oxygen radical absorbance capacity assay (ORAC), and anti-inflammatory assays using lipoxygenase (LOX) and xanthine oxidase (XO) assay. Besides that, total phenolic content (TPC), phytochemical screening and high-performance liquid chromatography (HPLC) analysis and gas chromatography-mass spectrometer (GCMS) were also carried out. MEDL exhibited significant (p<0.05) hepatoprotective activity against both inducers. Pre- treatment of MEDL at a high dose markedly attenuated the increase in serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) and prevented a marked decrease in superoxide dismutase (SOD) and catalase (CAT) levels in CCl4-and PCM-induced hepatotoxic rats. These observations were supported by the histologic findings and scoring, where the liver tissues in groups pre-treated with MEDL and Silymarin showed mild necrosis and inflammation of the hepatocytes compared to the DMSO pre-treated group (negative control group). For the partition extracts, EADL partition exhibited the best activity in protecting the liver against PCM-induced toxicity. Interestingly, EADL, at a low dose (50 mg/kg) significantly (p<0.05) reduced ALP, ALT and AST to 198.5 ± 19.78 U/L, 108.7 ± 29.00 U/L and 313.0 ± 65.99 U/L, respectively and the total bilirubin levels (1.133 ± 0.1687 umol/L) in PCM-induced hepatotoxic rats. EADL also increased the activity of SOD (17.98 ± 0.09 U/g tissue) and CAT (116.9 ± 2.71 U/g tissue) while significantly attenuated the malondialdehyde (MDA) levels of the liver to 2.61 ± 0.70 μM in the liver homogenates. EADL partition also ameliorated histopathological changes to liver tissues by the PCM intoxication. In the in-vitro antioxidant assay, MEDL showed the highest DPPH- and superoxide anion-radical scavenging activity (98.94 ± 1.14% and 93.2 ±1.18%) as well as high TPC (1757.25 ± 29.39 mg/100g GAE) and ORAC ( 24 272.50 ± 2056.53 μM TE/ 100g) values, indicating a high antioxidant activity. In addition, EADL with low TPC (352.18 ± 48.40 mg/100g GAE) exhibited a high scavenging activity against DPPH- and superoxide anion with 93.68 ± 3.0% and 92.6 ± 2.17%, respectively. EADL was also the highest in ORAC value with 555 000 ± 12 700 μM TE/ 100g. The phytochemical screening of MEDL and EADL showed the present of saponins, flavonoids, tannins and polyphenolic compounds. HPLC analysis of MEDL also identified the presence of flavonoids, Rutin and Quercetin in the extracts. Moreover, GCMS analysis revealed the presence of 48 volatiles compounds in the MEDL extracts with some of them reported to exhibit antioxidant and anti-inflammatory activity. MEDL and EADL also exerted hepatoprotective activity that could be partly contributed by its antioxidant activity and high phenolic content, and the presence of various bioactive compounds that might act synergistically to enhance the hepatoprotective effect.